Potent anti-proliferative effects against oral and cervical cancers of Thai medicinal plants selected from the Thai/Lanna medicinal plant recipe database "mANOSROI III" - Aranya Manosroi (2018)
© 2015 Informa Healthcare USA, Inc. Thai/Lanna medicinal plant recipes have been used for the treatment of several diseases including oral and cervical cancers. Objective: To investigate anti-proliferative activity on human cervical (HeLa) and oral (KB) cancer cell lines of medicinal plants selected from Thai/Lanna medicinal plant recipe database "MANOSROI III". Materials and methods: Twenty-three methanolic plant crude extracts were tested for phytochemicals and anti-proliferative activity on HeLa and KB cell lines for 24h by the sulforhodamine B (SRB) assay at the doses of 1×10 -1 ×10 -6 mg/ml. The nine extracts with the concentrations giving 50% growth inhibition (GI50) lower than 100μg/ml were further semi-purified by liquid/liquid partition in order to evaluate and enhance the anti-proliferative potency. Results: All extracts contained steroids/triterpenoids, but not xanthones. The methanolic extracts of Gloriosa superba L. (Colchinaceae) root and Albizia chinensis (Osbeck) Merr. (Leguminosae-Mimosoideae) wood gave the highest anti-proliferative activity on HeLa and KB cell lines with the GI50 values of 0.91 (6.0-and 0.31-fold of cisplatin and doxorubicin) and 0.16μg/ml (28.78-and 82.29-fold of cisplatin and doxorubicin), respectively. Hexane and methanol-water fractions of G. superba exhibited the highest anti-proliferative activity on HeLa and KB cell lines with the GI50 values of 0.15 (37-and 1.9-fold of cisplatin and doxorubicin) and 0.058μg/ml (77.45-and 221.46-fold of cisplatin and doxorubicin), respectively. Discussion and conclusion: This study has demonstrated the potential of plants selected from MANOSROI III database especially G. superba and A. chinensis for further development as anti-oral and cervical cancer agents.